Pemberian Rekomendasi Tempat Kuliner Bagi Pelajar dan Mahasiswa menggunakan Metode Fuzzy Mamdani - Diana Pratiwi; Sari Marito Tondang; Ayu Fadilla (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2020)
Culinary is a part of life that is closely related to daily food consumption. Some people have difficulty in determining where to eat to be visited, this is influenced by several considerations including the budget (budget) that is owned and the facilities at the place to eat. This article aims to recommend good culinary places for students, and students who are chosen from a good budget and facilities. The title of this article is proposed so that students can choose a good culinary place by using the Fuzzy Mamdani inference method. This method can be used to quickly complete this article. The limitations of planning a conventional food menu can be overcome in a number of ways, for example by increasing food menu data and by utilizing advances in information technology to find out food menus can be easily found on the internet.